2001
DOI: 10.1002/j.1556-6676.2001.tb01962.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Mistrust, Ethnic Identity, Racial Identity, and Self‐Esteem Among Ethnically Diverse Black University Students

Abstract: Cultural mistrust, ethnic identity, racial identity, and self‐esteem were examined among African (n = 26), African American (n = 110), and West Indian/Caribbean (n = 24) university students. African American students' scores were statistically different from those of African and West Indian/Caribbean students on cultural mistrust, racial identity, and ethnic identity measures. There were no statistically significant differences on self‐esteem among the 3 groups. Results did indicate that cultural mistrust, eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 18 publications
(10 reference statements)
7
104
0
Order By: Relevance
“…For example, Cross"s (1971) early work detailing Black identity, or the process of becoming Black, has been expanded extensively within the past decade and has since become the most widely researched of the ethnic identity models (Phelps, Taylor, & Gerard, 2001). This has resulted in several different models of racial and ethnic identity development that can be utilized in clinical settings when working with African American clients to describe the process by which an individual develops an identity as a person of color (Atkinson, Morten, & Sue, 1998;Helms, 1990;Phinney, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Cross"s (1971) early work detailing Black identity, or the process of becoming Black, has been expanded extensively within the past decade and has since become the most widely researched of the ethnic identity models (Phelps, Taylor, & Gerard, 2001). This has resulted in several different models of racial and ethnic identity development that can be utilized in clinical settings when working with African American clients to describe the process by which an individual develops an identity as a person of color (Atkinson, Morten, & Sue, 1998;Helms, 1990;Phinney, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Differences in these implicit representations may promote mindsets and distrust that in turn affect the nature and frequency of interactions between individual members of different groups (Feagin & McKinney, 2003). Using black and white as terms to describe racial identity groups, Phelps, Taylor and Gerard (2001) suggest that the mistrust between black and white individuals manifests ostensibly in "business and work, interpersonal, and social relations" (p. 209). These conditions may negatively impact and limit the development of the types of inter-group relations necessary to mitigate racial/ ethnic bias in organizations (Hilton & von Hippel, 1996).…”
Section: Group Categorizationmentioning
confidence: 99%
“…For example, the findings of two comparative studies that examined Black immigrants' attitudes with African Americans' attitudes found that cultural factors may explain why Black immigrants are less likely to perceive racial discrimination (Phelps, Taylor, Gerard, 2001;Phinney & Onwughalu, 1996). One study revealed that Black immigrants have more positive attitudes toward other racial groups than African Americans and are less mistrustful of Whites than African Americans (Phelps et al, 2001). The other study revealed that Black immigrants were more likely to identify with the traditional American values, including justice, equal rights, and equal opportunity than African Americans (Phinney & Onwughalu).…”
Section: Secondary Research Question 3: What Processes Do West Indianmentioning
confidence: 99%